Postnatal growth in very low birth weight babies fed on exclusive human breast milk - Bhattacharya, Abhijit; Dhingra, Sandeep; Adhikari, Krishna M. (International Journal of Contemporary Pediatrics, 2021)
Background: Ideal preterm nutrition should sustain growth which mirrors the intrauterine fetal growth rate. Human milk provides complete nutrition to term infants and has been recommended as the exclusive source of feeding till first 6 months. Concern regarding growth faltering in preterms has precluded exclusive use of human milk for nutrition. The aim of this study was to document the growth rates of preterms fed exclusive human milk from birth to discharge from hospital. Methods: This was a longitudinal cohort study in which all preterms admitted to neonatal intensive care unit (NICU) with very low birth weight (VLBW) and gestational age of ≤35 weeks were enrolled consecutively over a one-year period. Fluid, electrolyte and human milk intake was managed as per the NICU protocol. Vitamins and mineral supplements were added as per unit policy. Pre-feed weight, occipito-frontal circumference, and length was recorded at pre-determined intervals till discharge. Results: Data of 37 infants was analysed. The most common morbidity was respiratory distress (29.73%) followed by birth asphyxia. Average time to regain birth weight was 13.61 days while mean increase in weight, length and OFC was 11.24 gm/kg/day, 0.60 cm/week and 0.59 cm/week respectively. The NICU length of stay varied from 9-76 days. Conclusions: Exclusive use of human milk is reliable in achieving growth in preterm VLBW babies. Though the rate of growth is not comparable to intrauterine growth rates, nevertheless in the absence of accepted standards for postnatal growth in preterms on exclusive human milk, the results are reassuring.